Quantitative computational fluid dynamic analyses of oil droplets deposition on vaneless diffusor walls of a centrifugal compressor. Issue 3 (29th November 2019) - Sun, Liwei; Ma, Chaochen; Song, Panpan; Zhang, Hang
Abstract: In the vehicle turbocharger operating process, the diffusor walls are susceptible to oil droplet deposition. This deposition may cause deterioration in the diffusor flow performance, consequently resulting in the deterioration of compressor performance. In this paper, a three‐dimensional steady computational fluid dynamic (CFD) numerical investigation was performed to study droplet deposition on the walls of a centrifugal compressor diffusor. Firstly, the theoretical basis of oil droplet distribution and formation on the diffusor were presented. On the basis of these, the distribution rules of the capture efficiency and particle concentration for the diffusor were investigated considering six different droplet diameters (0.25 μm, 0.5 μm, 0.75 μm, 1.00 μm, 1.25 μm, 1.5 μm). The results indicate that the particle mass concentration on the hub side increased gradually, and the concentration on the shroud side decreased inversely. Furthermore, the area of high particle mass concentration focused on the small radius area of the hub side or at the downstream of the channel in the direction of the streamline. And the particle mass concentration on the shroud is equally distributed. Finally, the combination of turbulent diffusion and inertial theory was proposed to analyze the mentioned phenomenon, and the droplet deposition mechanisms on the centrifugal compressor diffusor were summarized. Abstract : (1) The trend of the capture efficiency on the hub side of diffusor is increasing, and the trend on the shroud side is decreasing. (2)The DPM concentration on the hub is lower than that on the shroud side. (3)The peak of the contaminant concentration on the hub side of the diffusor is located in the small radius area. And the circumferential and radial distribution uniformity on the shroud side is higher than that on the hub side.